Understanding Structure and Agency as Commercial Determinants of Health; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Kelley Lee; Eric Crosbie (Kerman University of Medical Sciences, 2020)
The limited success to date, by the public health community, to address the dramatic rise in non-communicable diseases (NCDs) has prompted growing attention to the commercial determinants of health. This has led to a much needed shift in attention, from metabolic and behavioural risk factors, to the production and consumption of health-harming products by the commercial sector. Building on Lencucha and Thow's analysis of neoliberalism, in shaping the underlying policy environment favouring commercial interests, we argue for fuller engagement with structure and agency interaction when conceptualising, assessing, and identifying public health measures to address the commercial determinants of health.